Salud, enfermedad, atención y cuidados: Miradas desde las ciencias sociales - Pagnamento, Licia (Estudios/Investigaciones, 2021)
Health, illness, medical attention and health care: Views from the social sciences: This book presents, in abbreviated form, the results of research carried out by a group of sociologists and social anthropologists who, while addressing diverse problems, reflect on social processes related to health, disease, medical attention and health care. The research was carried out in the region of La Plata (province of Buenos Aires) and addresses two major general areas: the first one, related to health policies, medical attention and health care processes, particularly oriented to vulnerable sectors (due to living conditions and age), and the second one, more related to the connections between gender and health, which explores issues related to childbirth, young parenthood in vulnerable sectors and transgender body modifications.